2010
DOI: 10.1159/000313868
|View full text |Cite
|
Sign up to set email alerts
|

Nexframe Frameless Stereotaxy with Multitract Microrecording: Accuracy Evaluated by Frame-Based Stereotactic X-Ray

Abstract: Objective: The development of image-guided systems rendered it possible to perform frameless stereotactic surgery for deep brain stimulation (DBS). As well as stereotactic targeting, neurophysiological identification of the target is important. Multitract microrecording is an effective technique to identify the best placement of an electrode. This is a report of our experience of using the Nexframe frameless stereotaxy with Ben’s Gun multitract microrecording drive and our study of the accuracy, usefulness and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…This resulted in an average 2.8 ± 0.4 mm vector deviation from the surgical plan (i.e. 3D or Euclidean distance; see Table 1 for individual values), which is consistent with prior assessments of DBS lead implantation accuracy in humans using similar neurosurgical methods [42][43][44]. Therefore, it is feasible to implant DBS leads into the sheep brain with at least as much accuracy as is performed clinically.…”
Section: Feasibility Of Routine Dbs Targeting the Sheep Stnsupporting
confidence: 81%
“…This resulted in an average 2.8 ± 0.4 mm vector deviation from the surgical plan (i.e. 3D or Euclidean distance; see Table 1 for individual values), which is consistent with prior assessments of DBS lead implantation accuracy in humans using similar neurosurgical methods [42][43][44]. Therefore, it is feasible to implant DBS leads into the sheep brain with at least as much accuracy as is performed clinically.…”
Section: Feasibility Of Routine Dbs Targeting the Sheep Stnsupporting
confidence: 81%
“…Yet, the increased procedural complexity does influence neurosurgeons' attitudes toward this operation. It was reported that the frameless system was inconvenient to use and was even left unused in some institutions [23,26,40,44]. …”
Section: Discussionmentioning
confidence: 99%
“…To compare the targeting accuracy, the Euclidean error d and its standard deviation SD d are adopted in this study. In some articles, only vector errors were reported [17,19,37,38,39,40]. In this situation, d was acquired with vector errors using equation 1 [18,29,31].…”
Section: Methodsmentioning
confidence: 99%
“…They reported a 2.65-mm (CRW) euclidean error with 70 leads and a 2.78-mm (Nexframe) euclidean error with 69 placed leads. Finally, the study by Fukaya et al [14] did not calculate euclidean errors. They only reported absolute errors due to the small number of evaluated lead placements (10 placed leads with Nexframe).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on accuracy of frame-based and Nexframe systems have shown variable results [9,10,11,12,13,14]. Comparison between studies is limited due to differences in sample sizes and methods used to determine lead location.…”
Section: Introductionmentioning
confidence: 99%